Molecular dynamics framework coupled with smoothed particle hydrodynamics for quantum plasma simulations - Thomas Campbell; Pontus Svensson; Brett Larder; Daniel Plummer; Sam M. Vinko; Gianluca Gregori (Physical Review Research)
We present a scheme for modeling quantum plasmas in the warm dense matter regime via a hybrid smoothed particle hydrodynamic–molecular dynamic treatment, here referred to as “Bohm SPH.” This treatment is founded upon Bohm's interpretation of quantum mechanics for partially degenerate fluids, does not apply the Born-Oppenheimer approximation, and is computationally tractable, capable of modeling dynamics over ionic timescales at electronic time resolution. Bohm SPH is also capable of modeling non-Gaussian electron wave functions. We present an overview of our methodology, validation tests of the single particle case including the hydrogen 1s wave function, and comparisons to simulations of a warm dense hydrogen system performed with wave packet molecular dynamics.